Mastering Roblox coding : the unofficial guide to leveling up your Roblox scripting skills and building games using Luau programming - Kiepe, Mark (Packt Publishing, Limited, 2022)
Discover how to build enhanced feature-filled games using the power of Luau programming by getting hands-on with creating a complete end-to-end game using Roblox Studio Key Features Leverage the tips and tricks covered in this game development book for writing advanced Roblox scripts Explore the capabilities of Roblox Luau to create complex games using user input, datastores, and user interfaces for all devices Each subject contains an additional exercise for the reader to experiment Book Description Roblox is a game platform with over 47 million daily active users. Something unique to Roblox is that you're playing games made by other gamers! This means that you can make your own games, even if you have no experience. In addition, Roblox provides a free engine that allows you to create and publish a simple game in less than five minutes and get paid while at it. Most Roblox games require programming. This book starts with the basics of programming in Roblox Luau. Each chapter builds on the previous one, which eventually results in you mastering programming concepts in Lua. Next, the book teaches you complex technologies that you can implement in your game. Each concept is explained clearly and uses simple examples that show you how the technology is being used. This book contains additional exercises for you to experiment with the concepts you've learned. Using best practices, you will understand how to write and build complex systems such as databases, user input controls, and all device user interfaces. In addition, you will learn how to build an entire game from scratch. By the end of this book, you will be able to program complex systems in Roblox from the ground up by learning how to write code using Luau and create optimized code. What you will learn Understand and learn the basics of Roblox Luau Discover how to write efficient and optimized Luau code to avoid bad smells Explore how to optimize your game for PC, consoles, phones, and tablets Get up to speed with how to build databases using Luau Understand client and server functionalities and learn how to securely establish communication Discover how to build an advanced Roblox game from scratch Who this book is for This book is for fairly experienced Roblox developers who have basic programming knowledge and want to take their skills to the next level with advanced concepts in a simple and effective way. Basic knowledge of Roblox, Roblox Studio, and Roblox Luau is recommended before getting started with this book. A short refresher is provided for those who have not used Roblox in a while.